2020
DOI: 10.1021/acs.nanolett.9b04841
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transport of Shape and Rigidity-Tuned α-Lactalbumin Nanotubes across Intestinal Mucus and Cellular Barriers

Abstract: Mucus is a viscoelastic biological hydrogel that protects the epithelial surface from penetration by most nanoparticles, which limits the efficiency of oral drug delivery. Pursuing highly efficient, biocompatible, and biodegradable oral drug vehicles is of central importance to the development of promising nanomedicine. Here, we prepared five peptosomes (PSs) with various sizes, shapes, and rigidities based on self-assembly of amphiphilic α-lactalbumin (α-lac) peptides from partial enzymolysis and cross-linkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(81 citation statements)
references
References 40 publications
1
80
0
Order By: Relevance
“…Thus, NP shape and elasticity may be closely intertwined in affecting the endocytosis of NPs. Based on the self-assembly of amphiphilic α-lactalbumin (α-lac) peptides from partial enzymolysis and cross-linking, Bao et al prepared peptosomes (PSs) with various shapes and rigidities [70]. The combined experimental results and the molecular simulations demonstrated that short nanotube exhibits the highest cellular uptake and transmembrane permeability.…”
Section: Shape and Elasticitymentioning
confidence: 99%
“…Thus, NP shape and elasticity may be closely intertwined in affecting the endocytosis of NPs. Based on the self-assembly of amphiphilic α-lactalbumin (α-lac) peptides from partial enzymolysis and cross-linking, Bao et al prepared peptosomes (PSs) with various shapes and rigidities [70]. The combined experimental results and the molecular simulations demonstrated that short nanotube exhibits the highest cellular uptake and transmembrane permeability.…”
Section: Shape and Elasticitymentioning
confidence: 99%
“…Practical application of α-LA nanotubes was demonstrated in the work of Bao et al [ 168 ]. They prepared five peptosomes of various sizes, shapes, and rigidities based on the self-assembly of α-LA peptides using partial enzymolysis and cross-linking.…”
Section: Fibrillation Of α-Lactalbumin; Nanoparticles and Nanotubementioning
confidence: 99%
“…To this end, we developed a set nanocarrier types with differing physical properties that were variously produced from hydrolyzed peptide fragments of α-lac. That is, building from previous understanding about how these α-lac peptide fragments can undergo a self-assembly process to produce nanostructures ( 26 , 27 ), we here systematically altered three separate production conditions to produce six different types of nanocarriers from the same starting material. The first condition that we altered was the controlled shape of the nanocarriers.…”
Section: Resultsmentioning
confidence: 99%